Matilda - Dahl, Roald; Blake, Quentin (Puffin London, 2016)
Matilda Wormwood's father thinks she's a little scab. Matilda's mother spends all afternoon playing bingo. And Matilda's headmistress, Miss Trunchbull? Well, she's the worst of all. She is a big bully, who thinks all her pupils are rotten and locks them in the dreaded chokey. As for Matilda, she's an extraordinary little girl with a magical mind - and now she's had enough. So all these grown-ups had better watch out, because Matilda is going to teach them a lesson they'll never forget